Comparative Study of Ion-Exchange and Biosorption Processes for the Removal of Cd and Zn Ions from Aqueous Effluents - Julia S. de Britto; Antonio Carlos A. da Costa; Aderval S. Luna; Cristiane A. Henriques (Adsorption Science & Technology)
A basic investigation of the removal of Cd(II) and Zn(II) ions from aqueous solutions by Sargassum sp. and NaY zeolite was conducted at room temperature under batch conditions. The results obtained indicated that, for both sorbents, cadmium and zinc ion uptake could be described by the Langmuir adsorption model. The kinetics of the biosorption process followed a pseudo-second-order model, whereas equilibrium in the ion-exchange process was attained so rapidly that the data obtained could not be modelled. The maximum uptake capacities of the sorbents studied were 120 mg/g biomass and 108 mg/g zeolite for cadmium ions and 45.5 mg/g biomass and 70 mg/g zeolite for zinc ions, respectively. This can be considered an excellent result compared with conventional adsorbent materials. Thus Sargassum sp. and NaY zeolite have a great potential for removing cadmium and zinc ions, especially when the concentrations of these ions are low as in wastewater stream samples.